2010
DOI: 10.1002/term.270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cross-linked chitosan microparticles for bone regeneration

Abstract: The objective of this preliminary study was to evaluate the applying of chitosan (CS)-based microparticles (MPs) in bone regeneration in vivo. The CS MPs were fabricated using our scale-up method, as previously described. Mesenchymal stem cells (MSC) were harvested from the femora and tibiae of Dark Agouti (DA) rats and seeded on CS MPs. An in vitro MSCs attachment experiment was conducted by trypsinizing the cells attached to the MPs at 5, 10, 20 and 30 h. Fluorescence images of MSCs attached to the MPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Direct encapsulation of cells during gel formation can be used to facilitate homogenous cell distribution in hydrogels. Numerous natural polymers including collagen [3], chitosan [21], and composite matrices [2225] have been employed to engineer tissues and have shown promise in bone regeneration[26]. A drawback of natural hydrogel materials is that they often lack mechanical strength and represent only the protein component of the native bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Direct encapsulation of cells during gel formation can be used to facilitate homogenous cell distribution in hydrogels. Numerous natural polymers including collagen [3], chitosan [21], and composite matrices [2225] have been employed to engineer tissues and have shown promise in bone regeneration[26]. A drawback of natural hydrogel materials is that they often lack mechanical strength and represent only the protein component of the native bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have adopted the fabrication procedure used by our group in previous studies [6, 10, 37, 40, 41]. The objective of this study was to obtain porous spherical scaffolds using chitosan, increase the mechanical strength of the scaffolds using nHA and characterized the scaffolds for its morphological, mechanical, physiochemical, cell attachment and cell cytotoxicity properties.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, numerous studies have reported that the mechanical and electrical properties of different polymers have improved when ZnO NPs are incorporated into the polymeric matrices [11][12][13]. Chitosan has been used for many different biomedical applications such as drug delivery and tissue engineering due to its favorable biocompatible and biodegradable properties [14,15].…”
Section: Introductionmentioning
confidence: 99%